(untitled) (LAPAI JOURNAL OF NIGERIA HISTORY, 2023)
This paper explores the theme of Integrated Qur’anic Education (IQE) in Niger State, focusing on the associated issues and prospects. As an integral aspect of the educational landscape, IQE combines conventional academic subjects with Quranic teachings, aiming to provide a holistic educational experience. The study investigates the challenges faced by the implementation of IQE in Niger State, shedding light on the socio-cultural, infrastructural, and policy-related impediments. The analysis addresses the socio-cultural factors influencing the acceptance and integration of IQE within the community, recognizing the significance of aligning educational practices with local norms and values. Additionally, the study delves into infrastructural impediments hindering the effective implementation of IQE, such as inadequate facilities and resource allocation. Furthermore, it critically examines existing policy frameworks, highlighting areas that require attention for the successful advancement of IQE in Niger State. It emphasizes the potential positive impact on fostering religious and cultural harmony, promoting moral values, and contributing to a well-rounded education. The major recommendations include a comprehensive curriculum that effectively integrates Qur’anic teachings with conventional subjects, ensuring a balanced and relevant educational experience.